The Effect of the Guided Inquiry Learning Model on Cognitive Learning Outcomes and Student Learning Activeness of Grade 10 Students at MA Miftahul Ulum Bettet - Malihatul Ainiyah; Moch Haikal (Lombok Institute, 2025)
This study was motivated by low science learning outcomes and the demands of 21st-century skills, which emphasize activeness, higher-order thinking, and students' independent engagement in the learning process. The study aimed to analyze the effect of the guided inquiry learning model on cognitive learning outcomes and student activeness among Grade 10 students at MA Miftahul Ulum Bettet, Pamekasan. A quantitative approach was employed using a quasi-experimental nonequivalent pretest–posttest control group design. The participants were female students in Grade X Science B (control: conventional/lecture-based instruction) and Grade X Science C (experimental: guided inquiry). Cognitive learning outcomes were measured using a five-item essay test, while student activeness was assessed using an observation sheet based on a rubric. Data were analyzed using Jamovi 2.0. Because the parametric assumptions were not met, the Mann–Whitney test was used for hypothesis testing. The results indicate that the experimental class achieved substantially higher mean cognitive posttest scores and activity scores than the control class, with statistically significant differences (p < 0.001) and a very large effect size. These findings suggest that guided inquiry is effective in improving students' cognitive learning outcomes and learning activity. It is therefore recommended as an alternative instructional model for Biology in Madrasah Aliyah (MA).